The resilient capacity in the professors of the Faculty of Commerce and Administration of Tampico - Gómez, Maria de Lourdes Arias; Gómez, Enrique Arias; Gómez, Jesús Arias; Arteaga, Lorena Gabriela Hernández; Negreros, María Elena Mendoza; Blanco, Azalea María Peña (Seven Editora, 2023)
Resilience is a term that is confused with resistance or survival, due to not having a clear idea of what resilience means, however, with or without knowledge of the meaning, the survey results do not reveal that most teachers are resilient, although for the majority of the teachers they had a number of problems both in their personal and work lives, they went ahead and fulfilled their duties. They realized that all problems have a positive side and leave a lesson from which they come out stronger. In general, the teachers felt overwhelmed by the circumstances and taught classes through a computer to a group of students who did not connect and if they did, they did not participate in class, in addition, most of the students cheated in the exams, for which, the knowledge they acquired was minimal. For this reason, the general objective of our research is: Analyze the resilient capacity of teachers at the Faculty of Commerce and Administration of Tampico. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-098